2017
DOI: 10.1016/j.egypro.2017.11.143
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Optimal measures for renovation of existing school buildings towards nZEB

Abstract: The energy policies of the European Union (EU) encourage the member states to convert building stock into nearly Zero-Energy Buildings (nZEB) and national public authorities to adopt exemplary actions. Directive 2010/31/EU (EPBD recast) introduces the concept of nZEB as a building that has a very high energy performance and its energy need is covered to a very significant extent by energy from renewable sources (RES). Moreover the Directive refers to the cost-optimal methodology for fixing building energy requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 1 publication
0
20
0
3
Order By: Relevance
“…It is obvious that the value of flood loss will be influenced by the affected building's geometry. Previous studies have confirmed that the building's geometry is related to numerous economic aspects, such as energy efficiency [31,32] and construction costs. The optimum shape of the building (walls, foundations) and the internal layout of the building were discussed in [33], with the objective of reducing construction costs.…”
Section: Introductionmentioning
confidence: 87%
“…It is obvious that the value of flood loss will be influenced by the affected building's geometry. Previous studies have confirmed that the building's geometry is related to numerous economic aspects, such as energy efficiency [31,32] and construction costs. The optimum shape of the building (walls, foundations) and the internal layout of the building were discussed in [33], with the objective of reducing construction costs.…”
Section: Introductionmentioning
confidence: 87%
“…Lucchi et al [12] M H R (historical) Mora et al [13] F H NR (school) D'Agostino et al [14] F/M H NR (school) Karásek et al [15] M H/DHW R/NR Bonakdar et al [16] F H/DHW R (multistory) Carpino et al [17] M H/C/DHW R (social housing) Loukaidou et al [18] F H/C R/NR (nZEB) Aelenei et al [19] Not indicated H/C/DHW NR (office) D'Agostino&Parker [20] F H/C/DHW/A R (two-story) Stevanović [21] Not indicated H/C NR (office) Baglivo et al [22] F/M H/C/DHW/A R (single-story) Zacà et al [23] M H/C/DHW/A R (multistory) Brandão De Vasconcelos [24] F/M H/C/DHW R (existing)…”
Section: Economic Scenario Energy Services Building Typologymentioning
confidence: 99%
“…For instance, in [12] a cost-optimal approach for the identification of suitable insulation materials to adopt in the refurbishment of historical buildings was carried out, but the analysis was limited to heating applications because the RB was located in the Prealps with a prevalent continental climate. A cost-optimal analysis aimed for the attainment of nZEB schools located in Northeast Italy was carried out in [13], considering only the heating requirements due to the particular intended use. A school building was also investigated in [14] to define the optimum insulation thickness and the best glazing system by locating the edifice in a mountain city of South Italy.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the energy-saving potential of the HVAC system was significant compared to the building envelope. Dalla Mora et al [6] studied an existing school building located in Italy, and several combinations of retrofit measures were applied to derive cost-effective solutions for renovation. Fonsca et al [7] designed a renovation plan for the Department of Electrical and Computer Engineering building in University of Coimbra, Portugal, with the aim to achieve the nearly zero-energy goal using two primary technologies: LED lighting and photovoltaic panels.…”
Section: Existing Energy Performance Of Education Buildingsmentioning
confidence: 99%